ANALISIS SISTEM ANTRIAN KASIR PADA MINIMARKET XYZ (Science and Technology (SciTech), 2022)
This study aims to determine the cashier queuing system at Minimarket XYZ. This study measures the performance of the queuing system through observation with a descriptive approach. After the data was obtained, the distribution test was carried out with POM-QM software. The results of this study indicate that the queuing model applied by Minimarket XYZ; the performance of the queuing system shows that the average customer arrival every hour is 25 people, the average customer served every hour is 26 people; and queuing system utilization shows steady state condition with 96.5%.